Memorandum of understanding between Universiti Teknologi MARA and Universitas Duta Bangsa / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2020)
UiTM and Universitas Duta Bangsa endeavour to take necessary steps to encourage and promote cooperation.